APLIKASI PENGOLAHAN DATA NOTULEN RAPAT PADA PROGRAM STUDI TEKNIK INFORMATIKA STMIK NURDIN HAMZAH JAMBI - Novhirtamely Kahar (JURNAL AKADEMIKA)
The minutes are brief notes on the report of the meeting. This study aims to establish a Data Processing System Application Minutes of Meetings In Engineering Program Information STMIK Nurdin Hamzah Jambi in order to simplify and speed up the data processing reporter minutes of the meeting on Informatics Engineering Program STMIK Nurdin Hamzah Jambi which has not been computerize. The system is built using the programming language Borland Delphi 7 and Microsoft Access 2007 as Database. The input data is the data lecturer informatics engineering course, meeting rooms, and meeting outcomes. The input data will be processed in the process of recording minutes of the meeting. While the output of the data report meeting minutes Informatics Engineering Program. The results showed that with the construction of the application system, the process of data processing and report creation data meeting minutes become easier, faster, and data recording errors can be avoided, so that the process of reporting to the Head of Department of Information Engineering STMIK Nurdin Hamza can be according to the schedule determined.